2023
DOI: 10.18632/aging.204542
|View full text |Cite
|
Sign up to set email alerts
|

ACSL1, CH25H, GPCPD1, and PLA2G12A as the potential lipid-related diagnostic biomarkers of acute myocardial infarction

Abstract: Lipid metabolism plays an essential role in the genesis and progress of acute myocardial infarction (AMI).Herein, we identified and verified latent lipid-related genes involved in AMI by bioinformatic analysis. Lipidrelated differentially expressed genes (DEGs) involved in AMI were identified using the GSE66360 dataset from the Gene Expression Omnibus (GEO) database and R software packages. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses were conducted to analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…An increased expression of ACSL1 has been found in different cancer types, associated with oncogenic functions in liver, colorectal, prostate, breast, and ovarian cancers [ 41 , 42 , 43 , 44 , 45 ]. Additionally, ACSL1 also plays an important role in cardiac and inflammatory diseases [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increased expression of ACSL1 has been found in different cancer types, associated with oncogenic functions in liver, colorectal, prostate, breast, and ovarian cancers [ 41 , 42 , 43 , 44 , 45 ]. Additionally, ACSL1 also plays an important role in cardiac and inflammatory diseases [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated the high expression of ACSL1, which reduces fatty acid β-oxidation by the peroxisome proliferator-activated receptor-gamma (PPAR-γ) pathway. 19 A cohort study has shown that expression of ACSL1 was significantly increased in the peripheral blood mononuclear cells of patients with AMI and may be a potential molecular biomarker for the early diagnosis of AMI. 20 It is reported that ALDH2 acts as a key mediator of endogenous cytoprotection against myocardial I/R injury, and ALDH2 activation is sufficient to protect the heart from ischemic damage.…”
Section: Discussionmentioning
confidence: 99%
“…In premenopausal women, high breast fat accumulation can produce and release inflammatory molecules implicit in vascular damage, atherosclerosis, leading to an increased risk of subsequent cardiovascular adverse events [ 5 ]. Lipid metabolism is of utmost importance in preserving a well-functioning cardiovascular system [ 6 ]. A study showed that metformin may reduce perimeter coronary fat levels by targeting the mediated-glucose cotransporter 2 (SGLT2)/leptin axis, improving adverse cardiovascular outcomes in diabetic patients [ 7 ].…”
Section: Introductionmentioning
confidence: 99%